Le indagini dell’Università di Firenze a Cosa. Dati ceramici preliminari: la ceramica a vernice nera, la terra sigillata e le anfore dall’incrocio tra le strade 5 e P : Black-gloss ware, terra sigillata, and amphorae from the ancient crossroad between streets P and 5. - Martina Rodinò; Contino , Alessia; D’Alessandro , Lucilla; Panariti , Dario (Rei Cretariae Romanae Fautorum Acta, 2024)
Since 2016 the University of Florence has stratigraphically investigated a sector of the Latin colony of Cosa (Ansedonia, GR, Italy). The new excavations have exposed the ancient crossroad between Streets P and 5, investigating a series of dumps that were leveled above the paved Roman road. The layers contained 2nd century pottery. The analysis of the pottery gives new insights into the history of the site and the commercial network and maritime trades in which Cosa is involved during the first and the mid-empire.